Peran Pemerintah dalam Mitigasi Kejahatan Pasar Modal Indonesia - Elvira Fitriyani Pakpahan; Bartolomeus Diaz Sianipar; Jessica Angkasa; Vivi Rahayu Sianturi; Sri Rahayu Hulu (Journal of Education, Humaniora and Social Sciences (JEHSS), 2019)
The large number of crimes that have occurred in capital market activities from 2009 to 2017 will caused a lot of speculation about the authority of the OJK agency responsible for modest market supervision so that this becomes a problem in this research. The problem is how the government plays a role in mitigating Indonesia's capital market crime. This study was conducted on the policies and performance of the Financial Services Authority. The research method used in this study is a litelature study, with a source of secondary legal material. Sanctions for capital market crimes are stated in the Capital Market Law that crime in the capital market can be prosecuted in the form of sanctions for acts against the law, and can also be prosecuted criminal. However, by the capital market regulator, the OJK tends towards compensation or fines/administrative sanctions.With capital market events, it is desirable for OJK to be able to make regulators that follow developments and conditions needed in capital market law enforcement, can minimize crime in the capital market and also doesn’t make investors both national & foreign afraid to take part in the capital market in Indonesia.